The Importance of Relationships in Patients with Irritable Bowel Syndrome: A Review - Mary-Joan Gerson; Charles D. Gerson (Gastroenterology Research and Practice)
Chronic illnesses such as irritable bowel syndrome are not experienced by patients in isolation. They live in a context of relationships, including spouses and partners, other family members, friends and business associates. Those relationships can have an effect, both positive and negative, on the course of illness and may also be affected by the experience of living with a chronic illness like IBS. We review the general literature regarding the effect of relationship factors on chronic illness followed by a focus on IBS symptomatology. We then discuss the challenges experienced by partners of IBS patients, followed by the effects of spousal violence, the particular relationship of mothers with IBS and their children, the effects of social support, and the importance of family dynamics and IBS. The final segment includes conclusions and recommendations. The topic, relationships and IBS, may have a significant effect on the lives of IBS patients and deserves more attention than it has received.